168k views
5 votes
Factorise the following.​

Factorise the following.​-example-1
User Pagliuca
by
6.7k points

1 Answer

3 votes

Answer:

x²(9x– 11)(9x + 11)

Explanation:

81x⁴ – 121x²

The expression can be factorised as follow:

81x⁴ – 121x²

x² is common to both term. Thus:

81x⁴ – 121x² = x²(81x² – 121)

Recall:

81 = 9²

121 = 11²

Therefore,

x²(81x² – 121) = x²(9²x² – 11²)

= x²[(9x)² – 11²]

Difference of two squares

x²(9x– 11)(9x + 11)

Therefore,

81x⁴ – 121x² = x²(9x– 11)(9x + 11)

User Wojteq
by
6.2k points